Evaluation of immunization coverage and its associated factors among children 12-23 months of age in Techiman Municipality, Ghana, 2016 - Martin Nyaaba Adokiya; Benjamin Baguune; Joyce Aputere Ndago (BMC, 2017)
Abstract Background In Ghana, Expanded Programme on Immunization administrative coverages are usually high while childhood immunization status remains low. Majority of children do not receive all the recommended 7 vaccines in 15 doses before 1 year of age. Surveys to validate administrative coverages and identify predictors of immunization status are not given the desired attention. Thus, the objective of this study was to evaluate the immunization coverage and its associated factors among children aged 12-23 months in Techiman Municipality, Ghana. Methods A cross-sectional cluster survey was conducted among 600 children. Data was collected using semi-structured questionnaire through face-to-face interviews. The tools were pre-tested in three communities with similar characteristics. The mothers/caregivers were interviewed and additional information extracted from child immunization cards. We observed the presence of Bacillus Calmette-Guerin scar on each child. Data was entered, cleaned and analyzed using Statistical Package for Social Sciences (SPSS) version 17.0. Descriptive statistics such as percentages, frequencies and cross tabulations performed using SPSS while bivariate and multivariate logistic regression analysis conducted using Stata 12.1 version to estimate the Odds Ratio of not being fully immunized. Results In total, 89.5% (537/600) of the children were fully immunized, 9.5% partially immunized and 1.0% received no vaccine. In the multivariate analysis, the following determinants were significantly associated with the likelihood of being not fully vaccinated (Odds Ratio (AOR) larger than 1) : age of the mother/caregiver 40-49 years (AOR = 0.15, 95%CI = 0.05-0.87) compared to less than 20 years; marital status (compared to never married/single: being married AOR = 0.29, 95%CI = 0.13-0.68), ethnicity (compared to the main ethnic group Akan: Frafra (AOR = 4.71, 95%CI = 146-15.18) and Kusaasi (AOR = 0.09, 95%CI = 0.02-0.51), religion (compared to Islam: Christianity AOR = 0.17, 95%CI = 0.06-0.50), sex of child (compared to male: female AOR = 0.39, 95%CI = 0.19-0.80) and possession of immunization card (compared to those having the card: those without the card AOR = 84.43, 95%CI = 17.04-418.33). Mothers/caregivers aged 40-49 years, being married, Kusaasi ethnic groups, Christian and female child have a higher likelihood of being fully immunized, while Frafra ethnic group and no immunization card have a higher likelihood of not being fully immunized. We found no association between immunization status and child's relationship to respondent; parity; education; occupation and child's age. Conclusion Immunization status (89.5%) and coverages ranged 92 to 99% of the vaccine doses is high compared to national and regional. Problems of not fully immunized persists and needs urgent attention. Education on immunization should be intensified by health providers. Moreover, disadvantaged populations should be reached with immunization services using out-reach activities.